Analysis of Factors Enhancing Students to Persist Studying in The Mathematics Education Study Program - Novia Isnaini Ramadina; Supriyo Supriyo (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
The sustainability of students' studies in the Mathematics Education Study Program is a crucial concern, especially amidst the various academic and non-academic challenges they face. This study aims to analyze the factors that motivate students to persist in studying in the Mathematics Education Study Program at Universitas PGRI Wiranegara (UNIWARA) Pasuruan, describe students' experiences in maintaining their study commitment, and identify the internal and external factors that most influence students' decisions to complete their studies. This study uses a qualitative descriptive approach with 17 active students selected through proportional random sampling. Data collection was conducted through questionnaires, semi-structured interviews, and documentation using method triangulation techniques. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that students' internal motivation is the most dominant factor that encourages them to persist in college, characterized by an interest in mathematics education, clear career goals, and personal commitment. These factors are strengthened by external support from family, lecturers, and peers, as well as students' resilience in facing academic challenges. The campus environment and administrative and academic systems play a role as supporting factors that help the study process run smoothly. The findings of this study indicate that student study sustainability is the result of an interaction between internal and external factors, with internal motivation as the main foundation in maintaining student commitment to study in the Mathematics Education Study Program.